POTENTIAL TOXICITY OF HEAVY METALS IN RAWADANAU WATERSHED - Dwindrata B Aviantara; Nida Sopiah (Jurnal Ecolab, 2009)
The study of the potential toxicity of five heavy metals: Cd, Cr, Cu, Fe, and Zn on human health of people livingin the Rawadanau Nature Reserve and its vicinity has been accomplished. Among the five studied heavy metalsonly cadmium and zinc demonstrated significant correlation of water levels and sediment contents of the heavymetals. Statistical analysis demonstrated water and sediment concentrations of either cadmium or zinc could becorrelated by r2 = 0.8622 or r2 = 0.8545 respectively. However, based on the suggested threshold value by WHO onthe permissible heavy metals ingested by human body, the water levels of cadmium which was found in the rangeof 0.01 – 0.05 mg L-1 posed more deleterious effects to human health than of zinc which was found in the range of0.02 – 0.18 mg L-1. Considering that the cadmium is a very toxic metal to biota then the exposure levels of peopleto the heavy metal must be avoided. This will call for stake holders of Rawadanau Nature Reserve to implementgood environmental management practices in order for sustaining Rawadanau as a water provider for industriesand public of Cilegon and Serang.